Pengaruh Product Quality , Brand Image Dan Product Variant Terhadap Kepuasan Pelanggan Mixue (Studi Kasus Pada Warga Kota Malang) - Achmad Muzakkiy; Mohammad Rizal; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The purpose of this study is to determine the influence of product quality, brand image, and product variants on Mixue customer satisfaction. The number of samples in this study was 80 respondents determined using the Malhotra formula with the characteristics that respondents are in Malang City and have purchased Mixue Ice Cream & Tea products. This type of research uses explanatory research and data analysis used is multiple linear regression analysis. The results of this study state that product quality, brand image, and product variants have a significant effect on Mixue customer satisfaction in Malang City partially and simultaneously. Keywords: Product Quality, Brand Image, Product Variant, Kepuasan Pelangan